2015
DOI: 10.1002/aic.14782
|View full text |Cite
|
Sign up to set email alerts
|

Design and screening of ionic liquids for C2H2/C2H4 separation by COSMO‐RS and experiments

Abstract: Ionic liquids (ILs) have been proposed as promising solvents for separating C 2 H 2 and C 2 H 4 , but screening an industrially attractive IL with high capacity from numerous available ILs remains challenging. In this work, a rapid screening method based on COSMO-RS was developed. We also present an efficient strategy to improve the C 2 H 2 capacity in ILs together with adequate C 2 H 2 /C 2 H 4 selectivity with the aid of COSMO-RS. The essence of this strategy is to increase molecular free volume of ILs and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 53 publications
2
67
0
2
Order By: Relevance
“…[43][44][45][46][47][48][49][50] A large number of ILs have been employed for the potential absorption separation of C 2 H 2 and C 2 H 4 . Zhao et al 51 have screened a new class of tetraalkylphosphonium ILs with high capacity and selectivity (0.476 mol/mol IL, selectivity up to 21.4) via a rapid screening method based on COSMO-RS. Palgunadi and Kim et al [52][53][54] reported the highly efficient selective removal of C 2 H 2 from C 2 H 4 by imidazolium-based ILs combined with various oxygen-containing anions such as dialkylphosphate ([Me 2 PO 4 ] 2 ), methylphosphonate ([MeHPO 3 ] 2 ), and acetate ([OAc] 2 , etc.).…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50] A large number of ILs have been employed for the potential absorption separation of C 2 H 2 and C 2 H 4 . Zhao et al 51 have screened a new class of tetraalkylphosphonium ILs with high capacity and selectivity (0.476 mol/mol IL, selectivity up to 21.4) via a rapid screening method based on COSMO-RS. Palgunadi and Kim et al [52][53][54] reported the highly efficient selective removal of C 2 H 2 from C 2 H 4 by imidazolium-based ILs combined with various oxygen-containing anions such as dialkylphosphate ([Me 2 PO 4 ] 2 ), methylphosphonate ([MeHPO 3 ] 2 ), and acetate ([OAc] 2 , etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the [P 4444 ]C 17 COO] has a very strong hydrogen‐bond basicity with a Kamlet‐Traft parameters β value up to 1.60, which is expected to be effective in adsorbing and activating both HCl and C 2 H 2 . Indeed, 1 mol [P 4444 ][C 17 COO] could adsorb 2 mol HCl at 453.15 K and 1 bar 17 and approximately 0.5 mol C 2 H 2 at 298.15 K and 1 bar . n‐tetradecane (C 14 ) was selected as the cosolvent due to its excellent thermal stability and low viscosity (0.41 mpas 298.15 K vs. 300 mpas of LCC‐ILs 293.15 K) and most importantly, its immiscibility with NPs@LCC‐IL even under 180°C (Supporting Information Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we reported that anion functional carboxylate ILs and hybrid porous materials containing anions exhibited an extraordinary capacity for C 2 H 2 absorption . And we developed an active and stable metal NPs/nanostructured IL system for C 2 H 2 hydrochlorination .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual screening involves generating thousands of potential structures and screening them for those structures that are predicted to have the desired properties. [13][14][15] The structure library to be virtually screened can be either a library of known and available compounds or a library of computer-generated structures, many of which have probably never been made. [1][2][3][4] However, outside of drug development, virtual screening is not a common practice.…”
Section: Introductionmentioning
confidence: 99%